Detection of the Carrier State in Hereditary Coagulation Disorders II - Veltkamp, J. J; Drion, E. F; Loeliger, E. A (Thrombosis and Haemostasis, 1968)
Specific determination of the coagulation factors makes it possible to demonstrate that heterozygotes of hereditary coagulation defects on the average display about 50% of the normal activity of the relevant coagulation factor. For the autosomally inherited defects, the published values of the coefficient of variation of the carrier population and the normal population show little disparity. It appears that discrimination of carriers of the factor II, V, VII, X, or XI deficiencies can be carried out with reasonable success. An exception, however, is the discrimination of carriers of haemophilia A and B. The large overlapping of the normal and the carrier distributions has been attributed to technical inadequacies in the assessment of factor VIII and IX activity and also to the possibly disturbing effect of the random inactivation of one of the two X-chromosomes (Lyon hypothesis). The statistical approaches described in the literature for the calculation of chance of carriership in individual cases are not accepted.Throughout the present investigation a one-stage method for the measurement of coagulation factor activity was used; this method was based on established principles, and adapted for use in Schnitger’s coagulometer. The experimental error (which with the two-stage method amounted to 25%) is 5.7% for factor VIII, 8.1 % for factor IX, and 7.3% for factor XII, expressed as the coefficient of variation of the result. This drastic improvement of the accuracy of the method was accomplished chiefly by automatic registration. The procedure is also more rapid and less tiring to perform than the two-stage method.The average factor VIII activity found in 30 proven carriers of haemophilia A was antilog 1.71 % (51 %) of normal. The standard deviation for this population was 0.21, as calculated from logarithms of the factor VIII activities, and the values were symmetrically distributed. For the normal population, which consisted of 60 persons, the standard deviation was 0.12. The biological variation of the factor VIII activity within the individual was 0.084 for carriers and 0.061 for normals; these values do not differ significantly.For the carriers of haemophilia B the average factor IX activity was antilog 1.7% (50%) and the standard deviation 0.13. The average activity in the normal population of 65 persons was antilog 2.007% (100.4%) and the standard deviation 0.105. There was a significant increase in factor IX activity with increasing age, at least for females. The variation within the individual was 0.066 for carriers and 0.0577 for normals.The wide variation within the populations of carriers of haemophilia A and B as compared to the normal population as well as to the populations of heterozygotes of autosomally inherited coagulation defects could be interpreted as support for the hypothesis of Lyon. This phenomenon could be caused, however, by different normal iso-alleles and the influence of other genetic or environmental factors.On the basis of our observations, it is possible to make the discrimination of carriers and normals on a 95% confidence level in the population of potential carriers of haemophilia A in 34% and of haemophilia B in 60% of the cases. The chance of carriership can be calculated for individual cases, with Bayes’ theorem, from the known chance of carriership on genetic grounds and the observed factor VIII or IX activity.The bimodal distribution of the results obtained in 50 obligatory heterozygotes for Hageman trait reflect the occurrence of two normal iso-alleles for the Hageman locus, one with 23% and the other 60% factor XII activity. The whole group still shows a mean activity of about 50% as compared to the normal population.Laboratory methods for measuring blood coagulation factors, adequate for the detection of heterozygotes of most autosomally inherited coagulation defects, have been shown to make only a modest contribution to the improvement of genetic counselling in haemophilia A and B. More fundamental approaches to the problem of discrimination of haemophilia carriers are required, because further standardization of the laboratory procedures cannot substantially improve the results obtained in this study. Theoretically, this problem will be easily solved when new common X-linked markers, closely linked to the haemophilia loci, are discovered.